Issues and Challenges Facing The Teaching and Learning of Tvet in The Covid-19 Pandemic Era - Madu Chika Madu; James Edomwonyi Edokpolor (Universitas Ahmad Dahlan, 2021)
This manuscript aims at discussing the issues and challenges facing the teaching and learning of Technical and Vocational Education and Training (TVET) in the COVID-19 pandemic era. Next, the manuscript discussed how stakeholders (e.g. governments, parents as well as TVET managers, lecturers and students can seize the opportunity to revamp TVET programme in the post COVID-19 era. Finally, the manuscript discussed the possible ways to overcome the issues and challenges facing TVET programmes in the COVID-19 pandemic era. Consequently, the authors drew logical conclusions on the discussions arising from the subject matter.